2017
DOI: 10.1111/tbed.12756
|View full text |Cite
|
Sign up to set email alerts
|

A G3P[13] porcine group A rotavirus emerging in China is a reassortant and a natural recombinant in the VP4 gene

Abstract: Group A rotaviruses (RVAs) are a major cause of serious intestinal disease in piglets. In this study, a novel pig strain was identified in a stool sample from China. The strain was designated RVA/Pig/China/LNCY/2016/G3P[13] and had a G3-P[13]-I5-R1-C1-M1-A8-N1-T1-E1-H1 genome. The viral protein 7 (VP7) and non-structural protein 4 (NSP4) genes of RVA/Pig/China/LNCY/2016/G3P[13] were closely related to cogent genes of human RVAs, suggesting that a reassortment between pig and human strains had occurred. Recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
(96 reference statements)
0
12
1
Order By: Relevance
“…For the NSP1 gene, RVA/Human/IND/Kol-066/2013/G9P4 and RVA/ Human/NPL/09N3140/2009/G12P[6] served as the major and minor parents, respectively, for genotypes A2 and A1. These results differed from those reported earlier for the VP4 and NSP1 genes of a novel human triple recombinant G4P[6-8_R] mono-reassortant strain identified in a stool sample from the Dominican Republic that showed two and three recombination breakpoints, respectively [21], and those for reported a porcine strain G3P [15] from China, which suggested that the strain was a natural recombinant in the VP4 gene (with breakpoints between 456-804 nt) [52]. The recombination in the VP3 gene detected in this study differed from that reported earlier from the USA for the strain RVA/Human-wt/AUS/CK20004/2000/G1P [8]P [4], which appeared to be a recombinant between genotype M1 and genotype M2, with four crossover points [12].…”
Section: Discussioncontrasting
confidence: 99%
“…For the NSP1 gene, RVA/Human/IND/Kol-066/2013/G9P4 and RVA/ Human/NPL/09N3140/2009/G12P[6] served as the major and minor parents, respectively, for genotypes A2 and A1. These results differed from those reported earlier for the VP4 and NSP1 genes of a novel human triple recombinant G4P[6-8_R] mono-reassortant strain identified in a stool sample from the Dominican Republic that showed two and three recombination breakpoints, respectively [21], and those for reported a porcine strain G3P [15] from China, which suggested that the strain was a natural recombinant in the VP4 gene (with breakpoints between 456-804 nt) [52]. The recombination in the VP3 gene detected in this study differed from that reported earlier from the USA for the strain RVA/Human-wt/AUS/CK20004/2000/G1P [8]P [4], which appeared to be a recombinant between genotype M1 and genotype M2, with four crossover points [12].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the RT-qPCR assay may be a useful alternative for the differential diagnosis of RV in possible coexisting mixed infections clinically indistinguishable such as those caused by other viral strains that cause gastroenteritis such as: astrovirus, coronavirus, picobirnavirus, calicivirus, among others as observed in the studies of Jing et al [60] and Waruhiu et al [61].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, unusual RVA genotypes have been frequently detected, such as: G3[P6], G12[P6], G8P[4], and G8P[6] and more recently the equine-like G3P[8] [ 17 , 23 , 24 ]. Similarly, recent studies from other countries have reported the detection of rare RVA genotype combination [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 66%